The infrared K-band identification of the DSO/G2 source from VLT and Keck data. Issue Volume 9:Issue S303(2013) (22nd May 2014) - Eckart, A.; Horrobin, M.; Britzen, S.; Zamaninasab, M.; Mužić, K.; Sabha, N.; Shahzamanian, B.; Yazici, S.; Moser, L.; García-Marin, M.; Valencia-S., M.; Borkar, A.; et al.
Abstract: A fast moving infrared excess source (G2) which is widely interpreted as a core-less gas and dust cloud approaches Sagittarius A* (Sgr A*) on a presumably elliptical orbit. VLT Ks -band and Keck K ′-band data result in clear continuum identifications and proper motions of this ∼19 m Dusty S-cluster Object (DSO). In 2002-2007 it is confused with the star S63, but free of confusion again since 2007. Its near-infrared (NIR) colors and a comparison to other sources in the field speak in favor of the DSO being an IR excess star with photospheric continuum emission at 2 microns than a core-less gas and dust cloud. We also find very compact L ′-band emission (<0.1″) contrasted by the reported extended (0.03″ up to ∼0.2″ for the tail) Brγ emission. The presence of a star will change the expected accretion phenomena, since a stellar Roche lobe may retain a fraction of the material during and after the peri-bothron passage.